MODEL PEMBELAJARAN OTENTIK DALAM MATA PELAJARAN PAI - syaefudin achmad (Journal of Research and Thought on Islamic Education, 2019)
Islamic education is a very important subject to make the learners understand the religion of Islam perfectly. But in reality, the purpose of Islamic religious education subjects is not always achieved. The average learner only understands the theories in Islamic religious education subjects as well as practicing them. They have not been able to practise theory in everyday life. Authentic learning methods can be an alternative to mejudkan the objective of learning to study the Islamic education in the maximum. An authentic learning Model is a learning that allows students to explore, discuss, and establish meaningful concepts and relationships, involving real problems and projects relevant to learners and Implemented through several stages.